Covalent organic framework based lithium-ion battery: Fundamental, design and characterization. Issue 1 (January 2021) - Hu, Yiming; Wayment, Lacey J.; Haslam, Catherine; Yang, Xiye; Lee, Se-hee; Jin, Yinghua; Zhang, Wei
Highlights: The recent progress in design and study of COFs and COF-derived materials for rechargeable lithium-ion batteries (LIBs) is summarized. The COF-based cathode, anode and electrolyte studies, including design strategies for Li ion storage, are discussed. The current challenges and opportunities in the rapidly growing field of COF-based LIB development are presented. Abstract: Lithium-ion batteries have become a staple in modern technology. Development of the next-generation batteries with higher energy storage capacity, light weight, and long lifetime is highly dependent on the advancement of novel materials utilized in each battery component. A recently emerging approach has been to utilize Covalent Organic Frameworks (COFs) to rationally design cathode, anode, and electrolyte materials for LIBs. COFs have many desirable properties, such as porosity, robust backbone, and customizable structure, for applications in LIBs. In this review, we discuss the electrochemical characterization of lithium ion batteries, general COF design principles, and examples of COF-based cathodes, anodes, and electrolytes to highlight the great potential and current obstacles in this rapidly developing field. Graphical abstract: Image, graphical abstract